+0

# 3y^1/3 -2 = 4

0
478
2

3y^1/3 -2=4

Guest Jun 19, 2015

#2
+92253
+5

I like the way that you have done this anon, I just want to have a play with it :)

\$\$\\3y^{1/3} -2=4\\\\
3y^{1/3} =6\\\\
y^{1/3} =2\\\\
(y^{1/3})^3 =2^3\\\\
y=8\$\$

Mmm so you didn't really need to use logs but both our answers are good :)

Melody  Jun 19, 2015
Sort:

#1
+5

3*y^(1/3) - 2 = 4

3*y^(1/3) = 4 + 2 = 6

y^(1/3) = 6 / 3 = 2

1/3 * Log(y) = Log(2)

Log(y) = Log(2) / (1/3) = Log(2) * 3

Log(y) = Log(2^3)

y = 2^3 = 8

Guest Jun 19, 2015
#2
+92253
+5

I like the way that you have done this anon, I just want to have a play with it :)

\$\$\\3y^{1/3} -2=4\\\\
3y^{1/3} =6\\\\
y^{1/3} =2\\\\
(y^{1/3})^3 =2^3\\\\
y=8\$\$

Mmm so you didn't really need to use logs but both our answers are good :)

Melody  Jun 19, 2015

### 12 Online Users

We use cookies to personalise content and ads, to provide social media features and to analyse our traffic. We also share information about your use of our site with our social media, advertising and analytics partners.  See details